The Amenity Value of Sports Facilities: Evidence From the Staples Center in Los Angeles. (October 2021) - Keeler, Zachary T.; Stephens, Heather M.; Humphreys, Brad R.
U.S. cities have recently experienced a boom in new sports facility construction. Although these facilities can provide benefits to local residents, they may also generate negative externalities, making dwellings near a facility less desirable. Using a hedonic spatial difference-in-differences model, we analyze the impact of proximity to the Staples Center, a sports and entertainment venue in downtown Los Angeles, California, on house prices. Results indicate that the arena opening increased nearby house prices and that there were also positive "anticipation" effects associated with the announcement of the new arena location and local government approval.